Arshile Gorky: An Armenian in New York - Vasconcelos, Ana (2015)
Born in Armenia, the oldest Christian country in the world but nevertheless one of the youngest reinstated republics (1991) after the collapse of the Soviet Union, Arshile Gorky flew to the United States in 1920, where he chose to reinvent himself in the struggle to become an artist. This reinvention meant the creation of a persona with, or behind, which Gorky kept alive the artistic flame inside himself. Gorky became one of the most learned voices lecturing on contemporary European modernist artists and movements of the late nineteenth and early twentieth centuries in the United States (New York) without ever visiting Europe. Moreover, he was able to survive the traumatic events he underwent during the Armenian Genocide (1915-1919) to adapt to his new country and identity, to live through the years of the Depression and, eventually, to become the protagonistof a major artistic breakthrough. This paper proposes an insight into the experience of life and frame of work of this Armenian-American artist, whose simultaneously rich, traumatic, dislocated and reenacted life and work established one of the most fertile links between his middle‑eastern origins, his dreamed of Europe and the particular transit of his American artistic creation.